Smart mining - Majstorović Vidosav D.; Simeunović Vladimir R.; Stošić Dragan P.; Dimitrijević Sonja T.; Mitrović Radivoje M.; Mišković Žarko Z. (Tehnika, 2024)
Industry 4.0 has become a global strategic initiative of scientific and technological development, which was launched by the most developed industrial countries in the world, and today has gone the furthest in its implementation. In essence, it is a new model of application of information and communication technology, based primarily on their integration with the object of application (for example in mining - production (BTO), transport, maintenance, etc.). The development and application of the elements of Industry 4.0 in this area leads to the establishment of the smart mining (SM) model, the elements of which will be presented in this paper. As an illustration of the application of this model in our conditions, and for the "Drmno" surface mine, this paper will present a model of planning and maintenance management of ERP (production-technological resource planning) and MES (work order management) model for Industry 4.0 , which uses a private cloud computing model.